Stress‐Busting Program for Family Caregivers: Validation of the Spanish version using biomarkers and quality‐of‐life measures. Issue 2 (16th February 2022) - Arévalo‐Flechas, Lyda C.; Flores, Bertha "Penny"; Wang, Hanzhou; Liang, Hanyu; Li, Yan; Gelfond, Jonathan; Espinoza, Sara; Lewis, Sharon L.; Musi, Nicolas; Yeh, Chih‐Ko
Abstract: Hispanic family caregivers of people with dementia experience higher levels of stress compared to non‐Hispanic white caregivers. Long‐term stress causes depression, caregiver burden, cellular aging, and dysregulation of the immune, nervous, and endocrine systems. The purpose of this study was to determine the validity of the Spanish version of the English Stress‐Busting Program (SBP) for Family Caregivers by determining changes in quality‐of‐life measures and biomarkers. Thirty‐six caregivers completed the SBP in the language of their choice (14 Spanish‐speaking Hispanics [HS], 8 English‐speaking Hispanics [HE], and 14 non‐Hispanic English [NHE] speakers). Quality‐of‐life measures included the Perceived Stress Scale, the Screen for Caregiver Burden, and the Center for Epidemiologic Studies Depression Scale. Assessment of oral health and immunity included salivary flow rate, pH, buffer capacity, total protein, and secretory immunoglobulin A (sIgA). Indicators of stress (salivary cortisol), inflammation (C‐reactive protein), and cellular aging (leukocyte telomere length) were assessed. Following completion of the SBP, the Spanish‐speaking group had less depression and caregiver burden along with improved oral health and reduced cellular aging. When comparing baseline values to post‐intervention, all three groups showed significant improvement in subjective caregiver burden. When the data from all three groups were combined, biomarkers that showed improvement after nine weeks of SBP included the stress hormone cortisol, salivary pH, and leukocyte telomere length. The results indicate that the Spanish SBP reduces caregiver stress as assessed by quality‐of‐life indicators and biomarkers. The Spanish SBP can help to mitigate health disparities in Hispanic Spanish‐speaking caregivers.